Study tour, graphic organizers in critical thinking in college students - Menacho Carhuamaca, Jaime David (2021)
The present study was carried out in the perspective of a scientific analysis of the incidence of educational trips and graphic organizers in the critical thinking of the students of a Private University of Lima, 2020. It was developed within the quantitative approach, based on the causal correlational design. The population included 85 undergraduate students. The instruments used as the educational study trip questionnaire, graphic organizers questionnaire and the questionnaire called evaluated my critical thinking allowed to verify that there is a relationship between the variables. It was concluded that the educational trips and the graphic organizers influence the critical thinking of the students. Furthermore, there is evidence of a significant incidence of the educational trips and the graphic organizers in analyzing information, proposing alternative solutions and arguing their position. Therefore, it will give way to the measurement of the critical points that generate flaws in inferring implications and the actions will be measured and taken.